The Effectiveness of Internet Memes on Students’ Writing Achievement - Nanik Sri Rahayu; Ningrum, Nurhalisa Widya; Isnawati, Uzlifatul Masruroh (Universitas Islam Lamongan, 2025)
The purpose of this research is to determine whether or not seventh graders at SMPN 1 Sumbergempol can improve their descriptive writing skills by using online memes. In this quantitative study, the researcher used a quasi-experimental strategy. The results showed that the experimental group averaged 79.00 points whereas the control group averaged 70.81. In addition, the findings (Sig 2-tailed) demonstrated a 0.000 significant value. The significance level (0.000 < 0.05) is lower than the significant value (Sig 2-tailed). We may conclude that the Alternative Hypothesis (Ha) is correct and reject the Null Hypothesis (H0) based on the findings of the significance value (Sig 2-tailed). The results show that seventh graders at SMPN 1 Sumbergempol benefit significantly from using Internet memes to improve their descriptive writing skills. It can be concluded that internet Memes enable the students getting the ideas and lead them to the objects being described. Through the application of this media, students can easily create descriptive text based on images.